Development of STEM-Based Augmented Reality Media to Strengthen Adaptive Reasoning and Creativity Skills of Elementary School Students - Opidianto, Myo; Ellianawati Ellianawati; Arif Widiyatmoko (Universitas Negeri Semarang, 2025)
The ability of adaptive reasoning is greatly needed to develop cognitive skills in students through mathematical observations of an object and problems caused by the aspect of creativity often being neglected because of the focus on mastery of the material, with students' answers being brief without elaboration and explanation. This research background study aims to develop STEM-based Augmented Reality (AR) learning media to assess the adaptive reasoning and creativity skills of fifth-grade students in IPAS (Science and Social Studies Integration) subjects. The research subjects included validators, teachers, and students to evaluate the media's validity, practicality, effectiveness, and user response. Validation results indicated that the media was highly feasible, with scores from content validators at 96%, media experts at 91%, and language experts at 94%. Practicality was rated at 97% by teachers and 82% by students. Effectiveness was measured using validated pretest and posttest instruments, yielding Aiken’s V scores ranging from 0.91667 to 1.00, indicating a “very high” category. Student responses showed score improvements, particularly in adaptive reasoning indicators such as “evaluating the correctness of answers” and “drawing conclusions,” which increased from mean scores of 6.33 and 6.27 to 6.88 and 8.3, respectively. Creativity indicators remained relatively stable between pretest and posttest, with mean scores consistently above 11 across all components. Overall, the AR-based media is considered feasible and effective for implementation in learning, although the interpretation of results should be approached with caution.